THE PRINCIPLES OF NATIONALITY AND GENERAL HUMANITY IN THE NATIONAL IDEA IN EDUCATING YOUTH IN THE SPIRIT OF PATRIOTISM (Multidisciplinary Journal of Science and Technology, 2024)
in this article, the principles of nationalism and universality in the national idea in educating young people in the spirit of patriotism , the issue of the harmony of nationality and universality in the education of the young generation, the formation of moral culture in young people, the feeling of concern for the interests of the Motherland, the harmony of nationality and universality, and the primacy of universal human values based on their interdependence the means of influence are illuminated.